TEACHER’S STRATEGIES IN TEACHING SPEAKING TO STUDENTS AT SECONDARY LEVEL - Agung Ginanjar Anjaniputra (Journal of English and Education, 2013)
This study is aimed at portraying teacher’s strategies in teaching speaking to students at secondary level and recognizing students’ response towards the strategies by involving an English teacher and a class of 22 students. In collecting the data, classroom observation and interview were conducted to identify the strategies of teaching speaking, and questionnaire was administered to the students to gain the data about their response towards the strategies under the umbrella of descriptive research. The result revealed that the strategies used by the teacher were cooperative activities, role-play, creative tasks, and drilling. In the meantime, students’ response towards the strategies resulted in positive attitude as they responded that the strategies helped them to speak, as well as concerned oral production of students whose participation was emphasized. Keywords: Teaching strategies, the teaching of speaking, secondary level